Implementing children and young people’s participation in decision-making: The role of non-governmental organisations - Le Borgne, Carine (Centre for Research on Families and Relationships, 2017)
This briefing addresses how children and young people’s participation in decision-making at the community level can be meaningfully supported by non-governmental organisations (NGOs), using research findings from Tamil Nadu (in South India) and Scotland (UK).
Keywords: Children and young people's participation, decision-making, rights of the child